PERANAN LEMBAGA KEAGAMAAN AL-IRSYAD DALAM PENDIDIKAN DI INDONESIA - Muh. Dahlan Thalib; Bahtiar; Hamdanah (IAIN PAREPARE, 2018)
ABSTRACTThe leaders of the national movement with full consciousness want to changethe future of the Indonesian nation, so the agenda of the struggle is to organizenational education. One association concerning the advancement of educationis the association of al-Irsyad, a religious institution devoting its attention to thefield of education marked by the official opening of Madrasahs from primary tomiddle. Al-Irsyad managed to mobilize the intelligence of the Indonesian nationin the field of education is not limited only among the descendants of ArabMuslims but also citizens muslim Indonesia (native population). The main pointof instruction in the madrasah is to give priority to Arabic so that students canunderstand the teachings of Islam well. Al-Irsyad also strives to restore societyto the correct purification of Islamic teachings so that all forms of life activitiesand life of the people is always based on Al-Qur'an and Hadith which is moreemphasis on aqidah ketauhidan in order to realize the Muslim person and theIslamic community to keridhoan Allah swt.